A journey to West Kalimantan: all about arts, culture and architecture / Dr Asmah Alia Mohamad Bohari - Mohamad Bohari, Asmah Alia (Perpustakaan Tun Abdul Razak, 2023)
Universiti Teknologi MARA aims to realise the purpose of the Globally Renowned University in two years, and the Centre of Studies Art and Design, Architecture, Building, and Surveying (SSSPU). UiTM Cawangan Sarawak were eager to be a part of the journey. This international outbound and inbound mobility programme for lecturers and students will be the starting point for the SSSPU pinned on the world map. This book was written to tell the story of a mobility trip overseas that became part of the history of this study centre. How we felt, and what we learned through the expression of words and sketches. Exploring the land of Borneo, which is full of customs and cultures shared by three countries. This first mobility programme is the outbound venture to West Kalimantan. How exciting is that! A tremendous gratitude goes out to all those who have contributed to this program's success and publication of this book. May the blessings be with you always.